Power-Attitude-Interest of Stakeholoders in Developing Adolescent Health Promotion Media - Muthmainnah, - (International Journal of Innovation, Creativity and Change, 2020)
Background: The adolescent population in Indonesia is almost 30% of the total Indonesian population. This number is quite large and has the potential to become an asset if appropriately managed. At present, there is more and more risk of behavioural problems. This can be known from the number of news, cases, morbidity, and mortality due to risky behaviour such as high cases of HIV in adolescence, even the number of abortions is also mostly done by adolescents because of premarital sex and unwanted pregnancy. Therefore many sectors carry out adolescent health programs to improve adolescent health status. Health promotion media is one of the strategies in influencing program success. This study aims to identify the power, interests, and attitudes of various stakeholders in developing adolescent health promotion media. Methods: The research is a qualitative descriptive study through in-depth interviews and FGD. The total respondents involved were 22 people from various stakeholders involved in the development of adolescent health promotion media. Stakeholders involved from the government (health, education, religion, social, national narcotics institution), NGOs, media, parent representatives, and stakeholder providers (teachers from 10 high schools from 5 regions in Surabaya). Then the data were analyzed through thematic analysis approach. Results: Not all stakeholders have strong power, a positive attitude and active interest in developing adolescent health promotion media. Only 2 stakeholders (the health sector and NGOs) have the category of "saviour" because these stakeholders have a health program. Many stakeholders should be involved, but in reality, they still tend to overlap and some stakeholders even say that it is not important to have adolescent health promotion media. Stakeholder providers tend to have weak power and passive interest because adolescent health promotion media are usually given directly from stakeholder decision-makers. Conclusions: The development of adolescent health promotion media is the responsibility of various stakeholders who have programs with adolescents as the target groups. Adolescent health is a comprehensive health status from physical, mental, social, economic and spiritual. Therefore not only the health sector is responsible, but all sectors from various groups (decision-maker, provider, user, and representative). Synergy efforts through role optimization are one of the success strategies in developing adolescent health promotion media